2022
DOI: 10.1002/saj2.20408
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of soil microbial community and physicochemical properties between rice–fallow and rice–bean (green manure) rotation

Abstract: Rice (Oryza sativa L.)–fallow and rice–green manure rotation are two common ecological rotation modes in the Lower reaches of the Yangtze River Basin. In this study, based on a long‐term positioning field experiment, soil microbial community structure (bacteria and fungi) and physicochemical properties were investigated and compared to comprehensively evaluate the effects of rice–fallow (RF) and rice–bean (Vicia faba L.) (green manure, RB) rotation on soil health, thus providing scientific basis for the utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
(50 reference statements)
0
0
0
Order By: Relevance
“…Numerous studies have indicated the benefits of green manure rotation in enhancing soil fertility and increasing crop yields [30,46]. However, in this study, the rice grain yield was found to be highest in the rice-fallow rotation system, which contradicts our hypothesis regarding the highest yield in the rice-green manure rotation system.…”
Section: Effects Of Cropping Systems and Organic Fertilizers On Soil ...contrasting
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have indicated the benefits of green manure rotation in enhancing soil fertility and increasing crop yields [30,46]. However, in this study, the rice grain yield was found to be highest in the rice-fallow rotation system, which contradicts our hypothesis regarding the highest yield in the rice-green manure rotation system.…”
Section: Effects Of Cropping Systems and Organic Fertilizers On Soil ...contrasting
confidence: 99%
“…Specifically, we focused on three rice-based cropping systems: rice-wheat rotation, ricegreen manure rotation, and rice-fallow rotation. It is hypothesized that in a rice green manure rotation system, the ample application of organic fertilizers would result in the highest soil fertility and rice grain yield and increased microbial activity associated with carbon [30]. Additionally, we proposed that using organic fertilizers with lower carbon-tonitrogen ratios would further enhance these effects.…”
Section: Introductionmentioning
confidence: 99%